2017
DOI: 10.1038/srep41404
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Synthetase DHCR24 Induced by Insulin Aggravates Cancer Invasion and Progesterone Resistance in Endometrial Carcinoma

Abstract: 3β-Hydroxysteroid-Δ24 reductase (DHCR24), the final enzyme of the cholesterol biosynthetic pathway, has been associated with urogenital neoplasms. However, the function of DHCR24 in endometrial cancer (EC) remains largely elusive. Here, we analyzed the expression profile of DHCR24 and the progesterone receptor (PGR) in our tissue microarray of EC (n = 258), the existing EC database in GEO (Gene Expression Omnibus), and TCGA (The Cancer Genome Atlas). We found that DHCR24 was significantly elevated in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…DHCR7 was found to be an important regulatory determinate between cholesterol and vitamin synthesis, as cholesterol is able to accelerate the proteasomal degradation of DHCR7, which can result in the accumulation of 7DHC and an increased production of vitamin D ( 126 ). DHCR24, which was also affected by modulation of HE4 levels, is another enzyme in the cholesterol biosynthesis pathway ( 127 ). It interacts physically and functionally with DHCR7 ( 128 ) and has a number of different cellular functions including anti-inflammatory and antiapoptotic functions, as well as regulation of oxidative stress and cell differentiation ( 129 ).…”
Section: Steroid Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…DHCR7 was found to be an important regulatory determinate between cholesterol and vitamin synthesis, as cholesterol is able to accelerate the proteasomal degradation of DHCR7, which can result in the accumulation of 7DHC and an increased production of vitamin D ( 126 ). DHCR24, which was also affected by modulation of HE4 levels, is another enzyme in the cholesterol biosynthesis pathway ( 127 ). It interacts physically and functionally with DHCR7 ( 128 ) and has a number of different cellular functions including anti-inflammatory and antiapoptotic functions, as well as regulation of oxidative stress and cell differentiation ( 129 ).…”
Section: Steroid Biosynthesismentioning
confidence: 99%
“…It interacts physically and functionally with DHCR7 ( 128 ) and has a number of different cellular functions including anti-inflammatory and antiapoptotic functions, as well as regulation of oxidative stress and cell differentiation ( 129 ). DHCR24 has also been proposed to be involved in tumor progression, as its deregulation has been linked to prostate, ovarian, and urothelial carcinomas ( 127 ).…”
Section: Steroid Biosynthesismentioning
confidence: 99%
“…Firstly, cholesterol has been reported to play a role in the synthesis of estrogen and progesterone. 3β-Hydroxysteroid-Δ24 reductase (DHCR24), the nal enzyme in the cholesterol biosynthetic pathway, has been demonstrated to aggravate cancer invasion and progesterone resistance in EC (18). Additionally, dietary cholesterol consumption, including saturated fatty acid, unsaturated fatty acid, and cholesterol intake, in uences EC risk by regulating the production, metabolism, and excretion of endogenous hormones (6).…”
Section: Discussionmentioning
confidence: 99%
“…GO terms with Pvalue < 0.05 were selected and ranked by enrichment score (-log10 (P-value)). Among the BP terms, response to cholesterol, epithelial to mesenchymal transition, and base-excision repair have been reported to be associated with tumor (6,(18)(19)(20)(21). In MF terms, WNT-activated receptor activity and WNT-protein binding might play a role in tumors.…”
Section: Go and Kegg Pathway Analysesmentioning
confidence: 99%
“…Berisha et al (36) indicated that DHCR24 is one of the transcripts affected by bariatric surgery in obese DM patients, with enzyme activity being correlated with changes of body weight, fasting plasma glucose and glycosylated hemoglobin content. Although focusing on endometrial carcinoma, another study revealed that the enzyme encoded by DHCR24 was induced by insulin stimulation via signal transducer and activator of transcription 3, which sensitizes to insulin signaling (37,38). This mechanism is possibly associated with the pathology of diabetes due to its link with hyperinsulinemia (39,40).…”
Section: Discussionmentioning
confidence: 99%